Demobilising and Disengaging Violent Extremists: Towards a New UN Framework. Issue 1 (23rd October 2017) - Richards, Joanne
First and second generation programmes of Disarmament, Demobilisation and Reintegration (DDR), are no longer 'fit for purpose' in contexts of violent extremism. Recognising this, voices from within the United Nations (UN) system have recently called for the development of a practice framework combining DDR and Countering Violent Extremism (CVE). Drawing on examples from Nigeria and Somalia, this commentary outlines six issue areas where DDR and CVE overlap, and where further operational guidance is required. These issue areas are: safe passage; the handling of seized and captured weapons; risk assessment; the use of deradicalisation programmes; the reintegration of extremist offenders; and the links between DDR and rehabilitation programmes for extremist prisoners.